(untitled) (Journal of Atomic and Molecular Sciences, 2013)
Initial configuration plays an important role in molecular dynamics (MD) simulation. Based on ab initio MD simulation used widely, we here first introduce a global search method for the ground state structure of clusters. We think that during a simulation, each type of atoms in cluster should be in equivalent sites when we choose the initial configuration. Thus, our proposal is an improvement in eliminating the ``unequal" in traditional annealing technology, and the results should be more convinced. Moreover, our method can make us obtain all possible structures of clusters, and also get some new structures, which are left out by previous studies. As an illustrative application, we here examine the S_6 cluster and found many structures (e.g. D_3d, C_2v, D_3h, C_s and C_1). The geometrical parameters and vibrational frequencies are in agreement with experimental values.